Socioeconomic Status And Motivation Effect on Students' English Speaking Skill - Rezki Aulia Sabri; Radiah Hamid (International Journal of English Learning and Applied Linguistics (IJELAL), 2023)
The research aimed at finding out whether or not (1) there was a significant effect between socioeconomic status on students’ speaking skill, and (2) there was a significant effect between motivation on students’ speaking skill at second semester of English Department Universitas Muhammadiyah Makassar. The research method was Descriptive Quantitative Research. The data collected through questionnaires (to obtained students’ socioeconomic status and motivation) and lecturer's document (to obtained students’ speaking score). From the population of 61 students in Academic Year 2021/2022, the researcher chose 30 students as sample by using random sampling techniques. The data analyzed by using Multiple Liniear Regression Analysis in SPSS. The result of data analysis, it found 1) based on T-test, the results of socioeconomic status on students’ speaking skill were T-test 1.456 > T-table 1.703, indicating there was no significant effect of socioeconomic status on students’ speaking skill, 2) based on T-test, the results of motivation on students’ speaking skill were T-test 4.199 > T-table 1.703 indicating that there was no significant effect of motivation on students’ speaking skill, This research suggested that regardless of socioeconomic status, lecturer keep provide students’ motivation to learn, motivates students about the benefits of having speaking skills, such as getting good careers, transferring knowledge to other people, and travelling abroad.